Stochastic factors drive dynamics of ammonia-oxidizing archaeal and bacterial communities in aquaculture pond sediment - Dai, Lili; Yu, Liqin; Peng, Liang; Tao, Ling; Liu, Yanbin; Li, Gu (Frontiers in Microbiology, 2022)
Ammonia-oxidizing archaea (AOA) and bacteria (AOB) play an important role in nitrification, which is essential in the global nitrogen cycle. However, their dynamics and the underlying community processes in agricultural ecosystems under disturbance remain largely unknown. In this study we examined the spatiotemporal dynamics of AOA and AOB communities and analyzed their community processes in the sediment of aquaculture ponds across three different areas in China. We found some significant temporal changes in AOA and AOB community diversity and abundances, but no temporal changes in community composition, despite the significant variations in sediment properties between different sampling times. Nevertheless, significant differences were found for AOA and AOB communities between different areas. Distinct area-specific taxa were detected, and they were found to be important in determining the response of AOA and AOB communities to environmental factors. In addition, geographic distance was found to be significantly correlated with AOA and AOB community composition, which demonstrates that dispersal limitation could significantly contribute to the variations in AOA and AOB communities, and stochastic processes were found to be important in structuring AOA/AOB communities in aquaculture ponds. Taken together, our study indicates that the dynamics of AOA and AOB are based on their community characteristics in aquaculture pond sediment. Our results, for the first time, provide evidence for the dynamics of AOA and AOB communities being driven by stochastic factors in a disturbed environment, and might also be of use in the management of the aquaculture environment.